DATA VISUALIZATION AS A MEASURE TO IMPROVE THE EFFECTIVENESS OF SURFACE WATER QUALITY ANALYSIS - Ekaterina G. Larina (Водное хозяйство России: проблемы, технологии, управление)
The article shows the possibilities of data visualization for various samples using examples of hydrological and water management information. The efficiency of using some techniques (graphical representation of data, Shewhart control maps, box-and-whiskers diagram, and scattering diagram) for analyzing the results of water quality control of the Moscow river and some of its tributaries is demonstrated. It is shown that the methods of visual analysis allow you to visually display any changes in the quality of surface water and can become an effective tool in the organization of water use in the metropolis.